The Role of Pedagogy Assistance in Increasing Prospective Student Self-Efficacy in College Preparation - Agus Joko Prayitno; Jajat S. Ardiwinata; Nike Kamarubiani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
In the concept of lifelong education, there are certain principles that underlie various exercises, activities and engagements that can be considered as a contribution to values education, and these will form the basis for lifelong education programs and activities. Learning in lifelong education is recognized in different forms at each age stage and can contribute to their desire to enhance personal development and creativity as they age. This lifelong education is a contribution to opening up and increasing sophistication in broadening the understanding of certain values for all students, during their study period. Lifelong education seeks to explore ways and means by which students can be encouraged to develop and grow well as individual beings and social agents, throughout their lives. In the process of lifelong learning, parents as individuals can obtain information and knowledge informally during their lives as parents. Parents as two individuals who generally have biological and psychological attachments, and have material responsibility for children's education, have an important role in determining the steps of children's education. For this reason, the knowledge that parents have about education majors and career planning will greatly help children as prospective students in tertiary institutions to consider the best education they will take to achieve the careers that have been planned beforehand. There are several other considerations that support research related to methods of increasing parental knowledge about colleges and careers for children's career planning, namely a great opportunity for parents to continue learning so they can direct and plan their children's future careers appropriately and accordingly. This is closely related to the principle of lifelong education. This research will be conducted using a qualitative research approach. This approach is commonly used to view human behavior as having its own meaning and implications. Through this approach, the author wants to see how the influence of knowledge possessed by parents about college and career can help children plan their future career properly and precisely.